2011
DOI: 10.1007/s00221-011-2553-y
|View full text |Cite|
|
Sign up to set email alerts
|

Nonrenewal spike train statistics: causes and functional consequences on neural coding

Abstract: Many neurons display significant patterning in their spike trains (e.g. oscillations, bursting), and there is accumulating evidence that information is contained in these patterns. In many cases, this patterning is caused by intrinsic mechanisms rather than external signals. In this review, we focus on spiking activity that displays nonrenewal statistics (i.e. memory that persists from one firing to the next). Such statistics are seen in both peripheral and central neurons and appear to be ubiquitous in the CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 139 publications
3
65
0
Order By: Relevance
“…In their work, Chacron et al demonstrated that a slow external noise leaves relatively intact the short-range correlations, while destroying negative correlations at large lags, giving rise to small and slowly decaying positive correlations which dominate the asymptotic regime. On the other hand, across different neural systems it has been observed that the only significant SCC corresponds to the lag 1 [19,23], which reinforces the idea that a slow external noise would be an important part of the incoming signal, in addition to fast fluctuations. Theoretically, the analysis of the spike-count variance for IF neuron models driven by slow fluctuations were successfully carried out via a quasistatic approximation [34,36].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 55%
See 4 more Smart Citations
“…In their work, Chacron et al demonstrated that a slow external noise leaves relatively intact the short-range correlations, while destroying negative correlations at large lags, giving rise to small and slowly decaying positive correlations which dominate the asymptotic regime. On the other hand, across different neural systems it has been observed that the only significant SCC corresponds to the lag 1 [19,23], which reinforces the idea that a slow external noise would be an important part of the incoming signal, in addition to fast fluctuations. Theoretically, the analysis of the spike-count variance for IF neuron models driven by slow fluctuations were successfully carried out via a quasistatic approximation [34,36].…”
Section: Discussion and Concluding Remarkssupporting
confidence: 55%
“…The external current is composed by a static input and fast fluctuations. For this system, the dependence of the adaptation current on the past history, through the initial states of the adaptation process, facilitates the development of correlations between successive ISIs [6,[13][14][15]19]. In the regime of slight adaptation, we have shown that correlations share a general structure across different models.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations